Representative CO2 emissions pathways for China's provinces toward carbon neutrality under the Paris Agreement's 2 °C target - Han-Tang Peng; Da Zhang; Jun-Ting Zhong; Li-Feng Guo; Si-Yue Guo; Jun-Ling Huang; De-Ying Wang; Chang-Hong Miao; Xi-Liang Zhang; Xiao-Ye Zhang (Advances in Climate Change Research)
China has committed to achieving carbon neutrality by 2060. It is essential to develop representative CO2 emissions pathways at the provincial level that align with the national target to facilitate effective policy implementation and scientific research. To address inconsistencies between provincial aggregate emissions and national estimates, this study compares the 2021 CO2 emissions estimates of China's provinces from the bottom‒up emissions factor method and the top‒down atmospheric CO2 concentration inversion method. We find that these methods yield comparable results for the emissions from energy combustion and industrial processes at the provincial level. Based on a review of existing research on CO2 pathways for China's provinces, we propose a set of representative pathways for China's provinces. These pathways align with past practices of allocating national emissions intensity reduction targets to provinces and are consistent with the national Tsinghua‒CMA pathway. The proposed pathways require provinces to sequentially peak their emissions by 2030, followed by rapid emissions reduction. Compared to a reference scenario without the carbon neutrality target, these pathways would incur an estimated cumulative GDP loss of about 1% between 2020 and 2060. However, there are notable regional variations, with some regions in the northwest potentially experiencing higher economic growth due to the availability of high-quality low-carbon resources. We recommend that China enhance provincial-level CO2 emissions accounting by cross-validating bottom‒up and top‒down methods. Additionally, careful consideration should be given to aligning provincial targets with national and global commitments when updating pathways toward carbon neutrality.